2018
DOI: 10.1096/fj.201801672r
|View full text |Cite
|
Sign up to set email alerts
|

In vivo screening of multiple bacterial strains identifies Lactobacillus rhamnosus Lb102 and Bifidobacterium animalis ssp. lactis Bf141 as probiotics that improve metabolic disorders in a mouse model of obesity

Abstract: Given the growing evidence that gut dysfunction, including changes in gut microbiota composition, plays a critical role in the development of inflammation and metabolic diseases, the identification of novel probiotic bacteria with immunometabolic properties has recently attracted more attention. Herein, bacterial strains were first isolated from dairy products and human feces and then screened in vitro for their immunomodulatory activity. Five selected strains were further analyzed in vivo, using a mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 65 publications
(81 reference statements)
2
49
0
Order By: Relevance
“…Lactobacillus rhamnosus Lb102 and Bifidobacterium animalis ssp. lactis Bf141 isolated by Le Barz et al from fermented milk products and human feces, respectively, were used to interfere with mice fed with high-fat diet and it was found that they could effectively alleviate the onset of obesity and reduce the content of liver fat in mice (Le Barz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus rhamnosus Lb102 and Bifidobacterium animalis ssp. lactis Bf141 isolated by Le Barz et al from fermented milk products and human feces, respectively, were used to interfere with mice fed with high-fat diet and it was found that they could effectively alleviate the onset of obesity and reduce the content of liver fat in mice (Le Barz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Lactobacillus rhamnosus and B. animalis spp. lactis , have been shown to reduce diet‐induced weight gain and also improve insulin sensitivity and glucose tolerance in animal models . The present study aims to investigate the changes produced in gut microbiota by a weight‐loss program based on a VLCKD followed by a low‐calorie diet (LCD), as well as whether the use of synbiotics is able to modulate gut microbiota diversity and composition and its association with gut permeability and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus is one of the genera that are most commonly used as probiotics, which has exerted various beneficial functions on the host (Druart et al, 2014). L. rhamnosus GG was observed to ameliorate dextran sulfate sodium (DSS)-and oxazoloneinduced colitis through the activation of the epidermal growth factor receptor (EGFR) (Yan et al, 2011); the administration of L. rhamnosus LB102 reduced diet-induced obesity and inflammation, concomitant with the improvement of glucose tolerance and insulin sensitivity (Le Barz et al, 2019). L. murinus has also been reported to successfully colonize in rodent intestines and to possess protective properties for necrotizing enterocolitis (Isani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%